(untitled) (Architecture Image Studies, 2025)
This is the third special issue that Clear+Park (C+P) have edited for AIS, and working with them has once again been a hugely enjoyable experience. In all our collaborations, we have enjoyed enormous freedom in the type of projects that can be included, especially the license to mix practice-based projects and speculative approaches alongside more traditional academic text-led pieces. In this edition, we look at the technologies of digital capture: 3D scanning, photogrammetry and depth, and motion detecting technologies. The introduction of these instrumental forms of capture has allowed highly accurate processes by which objects and spaces can be surveyed, mapped and digitised. Currently, this information is predominantly used to catalogue, record and document spaces and artefacts as part of a digital project workflow, often within a construction or heritage context. Author Biographies Nic Clear, Professor of Architecture, Dean of School of Arts and Humanities, University of Huddersfield Professor Nic Clear is a qualified architect, writer and curator. He is Professor of Architecture and Dean of the School of Arts and Humanities at the University of Huddersfield. He was a Professor of Architecture and Head of the Department of Architecture and Landscape at the University of Greenwich, having previously taught at the Bartlett School of Architecture for over 20 years. In 2015, he was the Inaugural Professor for Research in Visionary Cities at the Institute of Fine Arts in Vienna, and has taught in the UK, Europe, the US and Canada. Hyun Jun Park, Course Director Postgraduate Architecture, Leeds Beckett University Hyun Jun Park is a practitioner, writer, curator, fellow of the Royal Society of Arts and Course Director for Postgraduate Architecture at the Leeds School of Architecture, Leeds Beckett University. Prior to this, he was Course Leader for the Master of Architecture at the University of Huddersfield and taught postgraduate M.Arch design studio at the University of Greenwich. Before he came to the UK, he was an associate architect at SAMOO Architects & Engineers (SAMSUNG Corp), Seoul, Korea. He was awarded M.Arch by the Bartlett School of Architecture and finished his BA and first master’s degree at Hongik University, Seoul, Korea. Clear + Park Clear+Park use 3D laser scanning to create multidisciplinary works that operate across architecture, installation, and media arts. Clear+Park use 3D scanning to capture spaces and create spatial representations and narratives that engage with, and respond to specific site histories and spatial practices. Through their research Clear+Park explore ways in which architects and artists can reproduce, develop, manipulate, and represent spaces using advanced digital technology in ways that engage with non-specialist audiences.